2022
DOI: 10.1186/s12960-021-00687-9
|View full text |Cite
|
Sign up to set email alerts
|

Workforce problems at rural public health-centres in India: a WISN retrospective analysis and national-level modelling study

Abstract: Background Rural India has a severe shortage of human resources for health (HRH). The National Rural Health Mission (NRHM) deploys HRH in the rural public health system to tackle shortages. Sanctioning under NRHM does not account for workload resulting in inadequate and inequitable HRH allocation. The Workforce Indicators of Staffing Needs (WISN) approach can identify shortages and inform appropriate sanctioning norms. India currently lacks nationally relevant WISN estimates. We used existing d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…1 ). Study characteristics [ 10 , 16 102 ] are described in detail in Supplementary Table 2 . The first research question was addressed in 30.6% of studies ( n = 27) whereas 69.3% of studies ( n = 61) addressed the second research question.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). Study characteristics [ 10 , 16 102 ] are described in detail in Supplementary Table 2 . The first research question was addressed in 30.6% of studies ( n = 27) whereas 69.3% of studies ( n = 61) addressed the second research question.…”
Section: Resultsmentioning
confidence: 99%
“…The thematic analysis of data regarding the second research question yielded five kinds of HRH-related problems that are causing a scarcity of HRH in India. The outcomes of each study are described in Supplementary Tables 3 and codes identified under each theme is shown in Supplementary Table 4 [ 10 , 16 102 ]. A summary of these themes is provided in Table 2 below:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, the general health of the people in rural populations is inferior to that of urban populations (31); rural areas tend to have shorter life expectancies and high mortality rates due to infectious diseases like tuberculosis (TB)(32). Despite these adverse statistics, while 72.2% of Indian people reside in rural areas, only 40.8% of healthcare workers are available for rural areas (33). Thus, it is imperative that public health management of rural populations in developing countries improves..…”
Section: Methods and Outcomesmentioning
confidence: 99%
“…As a result of public health systems' failure to offer access to high-quality care, private healthcare systems have developed at the same time, with their proportion of the market increasing steadily and gradually over time. As a result of the incapacity of public health systems to offer access to high-quality treatment, private healthcare systems have developed at the same time, with the continuous and gradual growth of private healthcare services over the last several decades (Nair et al, 2022).…”
Section: A Introductionmentioning
confidence: 99%